SINONIM ADJEKTIVA DALAM BAHASA MINANGKABAU DI KENAGARIAN KACANG KECAMATAN X KOTO SINGKARAK KABUPATEN SOLOK - Sabri, Ikram; Agustina, Agustina (Universitas Negeri Padang, 2019)
This study aims to describe: (1) the pair of adjective synonyms in Minangkabau Language at Kanagarian Kacang, District Â X Â Koto Singkarak, Solok Regency, and (2) types for the pair ofadjective synonymsin Minangkabau Language at Kanagarian Kacang, District X Koto Singkarak, Solok Regency. Type of this research is qualitative research with descriptive methods. Data of this research are adjectives in Minangkabau language in variety of oral and writing. The source of this research data are adjective synonyms in Minangkabau language. This research conducted in the community of Kanagarian Kacang, District X Koto Singkarak, Solok Regency. Result of this study concluded: (1) the pair of adjective synonyms in Indonesian language are standard adjectives in high percentage and non-standard adjectives in low percentage, and (2) four types of adjective synonyms in Minangkabau language are absolute synonymy, complete synonymy, descriptive synonymy, and near-synonymy.Keywords: synonyms, adjektive, language Minangkabau